Experimental and Numerical Investigation of SUP12 Steel Coil Spring - Zainal Abidin, M.I.; Mahmud, J.; Abd Latif, M.J.; Jumahat, A. (2013)
Coil springs made of spring steel often have high yield strength which enables them to return to their original form after a significant force is applied. Specific application of steel springin automotive is ruled by industrial guideline, for example, Japanese Industrial Standard (JIS), Daewoo Engineering Standard (EDS) and Daihatsu Technical Standards (DTS). This study attempt to investigate the characteristics of a coil spring type used in automotive i.e. SUP12 where the analysis approach was done systematically using experimental and numerical methods. The experimental part was intended to verify the SUP12 springs material properties (spring constant, yield strength and tensile strength) are within standard for spring steels, JIS G 4801(1984). The SUP12 spring underwent tensile testing in accordance to JIS Z 2201(2010). Later, finite element simulation was performed using HYPERWORKS (Ver. 11) software to predict the steel spring under displacement conditions as per specific customer requirement i.e. at full rebound, curb length and full bump. The resulting experimental data indicates that the tested SUP12 passed the minimum requirement as per standard. On the other hand, finite element results show that the spring meets the customer requirement within small deviation. This suggested that the systematic verification by experiment and numerical analysis approach on such spring is practical by spring maker.